Design And Analysis Of Filament- Wound Compressed Natural Gas Carbon Fibre - Reinforced Composite Tank - Mahmud Zuhud, Nurul Zuhairah (2008)

(untitled)
First ply failure (FPF) strengths of laminated composite tank subjected to uniform internal pressure loads are studied via both analytical and finite element analysis approaches. The filament-wound CNG carbon fibre reinforced composite tanks are designed with a T6-6061 aluminium cylinder with elliptical end closures acts as the liner which is overwrapped with high modulus carbon fibre-reinforced epoxy composite. The objectives of this study are to optimize the composite layer thickness and to optimize fibre orientation configurations of carbon fibre laminate as to have a lightweight and high performance filament-wound CNG carbon fibre-reinforced composite tanks. In analytical approaches, in order to predict the first-ply failure (FPF) pressure of filament-wound CNG carbon fibre-reinforced composite tanks, the stresses and strains throughout the laminate were determined using the classical lamination theory which were then used in three most common composite failure theories, that are the maximum stress theory, maximum strain theory, and quadratic or Tsai-Wu failure theory. Optimal general design of fibre orientations were then used to carry out in lay-up optimization or arrangement of composite layer stage to be used for filament winding process in order to study the effect of fibre orientation angles using an equal thickness of composite layer on the tank performance. The range of helical angles used is in between 0° to 60°, which is based on the traditional theoretical optimal helical angles from classical lamination theory. The ratio of 2:1 hoop to helical angles is used to predict the maximum first-ply failure (FPF) pressure. The optimization results gave the optimal fibre orientations of the [( ) ] 11 24 30 /− 30 / 90 with b/a = 1.093 for CNG 1, b/a = 1.110 for CNG 2 and b/a = 1.128 for CNG 3 which obtained were then used for stress analysis in finite element analysis using ANSYS version 7.1 software. The accuracy of the theoretical and finite element analysis of first-ply failure (FPF) pressure is verified by a verification study where a similar finite element model from literature have been modelled and analysed using similar method used to design filament wound CNG carbon fibrereinforced composite tanks in order to verify a valid finite element method used. The results were then being compared literature study.